2020
DOI: 10.2147/ccid.s235880
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy of a Dermocosmetic Serum Combining Bakuchiol and Vanilla Tahitensis Extract to Prevent Skin Photoaging in vitro and to Improve Clinical Outcomes for Naturally Aged Skin</p>

Abstract: Background: Skin aging is characterized by slacking and loss of density, especially under ultraviolet (UV) radiation exposure. Objective: To investigate the beneficial effects of a combination containing bakuchiol (BK) and vanilla tahitensis extract (VTE) to prevent skin photoaging in vitro and to improve clinical outcomes for naturally aged skin. Materials and Methods: Human dermal fibroblasts were treated with active compounds, exposed to an acute dose of UVA and analyzed by confocal microscopy: actin networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Actin network was evaluated with confocal microscopy, levels of IL‐8 and P‐16 expression were measured for inflammation and senescence. BAK alone prevented both actin network alteration and IL‐8 upregulation, while BK+VTE demonstrated synergistic protection against IL‐8 and p16 overexpression 10 . Also, an open‐label clinical trial was conducted in women applying this serum twice daily for 56 days, were skin remodeling, firmness, and radiance improved at the end of the trial 10 …”
Section: Resultsmentioning
confidence: 99%
“…Actin network was evaluated with confocal microscopy, levels of IL‐8 and P‐16 expression were measured for inflammation and senescence. BAK alone prevented both actin network alteration and IL‐8 upregulation, while BK+VTE demonstrated synergistic protection against IL‐8 and p16 overexpression 10 . Also, an open‐label clinical trial was conducted in women applying this serum twice daily for 56 days, were skin remodeling, firmness, and radiance improved at the end of the trial 10 …”
Section: Resultsmentioning
confidence: 99%
“…LCC is an ester obtained from the reaction of the coconut alcohol-derived fatty acids with a mixture of caprylic acid and capric acid 38 . Both caprylic acid and capric acid, as medium-chain fatty acids, can be extracted from coconut oil and have been used as ingredients for skincare formulation to protect against UV radiation 39 , 40 . It has been reported that addition of caprylic acid into the fermentation process enhanced acetate production 41 .…”
Section: Discussionmentioning
confidence: 99%
“…62 It also works synergistically with other natural compounds to reduce inflammation and protect and maintain naturally aging skin. 10 This higher tolerability allows bakuchiol to be an effective anti-aging treatment for people of all skin types. Furthermore, it can also be formulated for people with hyperpigmentation historically perceived as less tolerant of retinol.…”
Section: Anti-inflammatory Effects Of Bakuchiolmentioning
confidence: 99%
“…Bakuchiol can be combined with Vanilla tahitensis extract to inhibit skin photoaging and cause improvement in skin barrier function and elasticity, increasing cellular turnover and improving signs of aging. 10 A study by Bacqueville et al used an in vitro skin model made of human dermal fibroblasts treated with the compounds alone or in combination, after which they were exposed to an acute dose of UVA. Exposure to UVA-induced significant morphological changes and increased IL-8 and p16 expression in the control model (no treatment), suggesting inflammation and senescence.…”
Section: Combination Effectsmentioning
confidence: 99%
See 1 more Smart Citation